The Role of Homo Oeconomicus in the Political Economy of James Buchanan - Gebhard Kirchgässner (Center for Research in Economics, Management and the Arts (CREMA), 2014)
Whenever the economic model of behaviour is to be applied, the utility function has at least somewhat to be specified. Buchanan generally prefers to apply a rather narrow version. However, he acknowledges that it is hardly possible to explain actual behaviour of individuals with such a version, so in performing empirical economic research he accepts that we have to use a more open one. He also ac knowledges that people might be have differently in markets than they do in politics; other-regarding beha viour might be more pronounced in politics as compared to markets. Which version should be applied in constitutional economics, however, is a different question. Follo wing a long ongoing tradition in political philosophy, he insists that for methodological reasons the narrow version is the correct one to be applied; this is the way to compare different sets of rules when analysing the possible abuse of power by rulers in order to prevent it as far as possible. The same should also be taken into account when analysing the process of policy advice . The narrow Homo Oeconomicus model should, however, not be misunderstood as a normative prescription.
Keywords: B41; 330; Homo Oeconomicus; Economic Model of Behaviour; Empirical Public Choice; Constitutional Economics; Self-Interest; Policy Advice